Natural Products and Synthetic Derivatives as Promising Candidates Against Neglected Tropical Diseases - dos Santos Fuzaro, Ana Flávia; Sousa Ponciano, Carolina; Barros, José C.; M. Grazul, Richard; Vieira de Almeida, Mauro; Pereira Ávila, Eloah (Orbital: The Electronic Journal of Chemistry, 2022)
Neglected Tropical Diseases (NTD) are a group of endemic diseases that cause up to one million deaths annually. Leishmaniasis and Chagas Disease are classified as NTD whose current treatments are of limited access. There is an urgent need to develop new agents to combat or alleviate the symptoms of these pathologies. The present work highlights the activities of several natural products and their derivatives which have been tested against the causative parasites of both diseases. The activities of natural products illustrate their potential to assist in the combat against NTD. Research in this area could provide an opportunity to advance medical research and to provide treatments to low- and middle-income countries.